Optimizing source-sink relationships and photoprotective mechanisms in wheat to enhance photosynthetic efficiency and nitrogen management - Zhang, Siqi; Li, Xiaohui; Wang, Xinyu; Zhang, Jie; Li, Guoqiang; Tian, Zhongwei (Frontiers in Plant Science, 2025)
Although the source-sink relationship is an intrinsic factor affecting crop photosynthesis, the response of different source-sink types to nitrogen (N) availability in photoprotection and photosynthetic efficiency is still unclear. This study investigates the physiological mechanisms underlying differences in photosynthetic capacity and photoprotection in wheat with different source-sink relationships under varying N levels. Field experiments revealed that compared to sink-limited wheat (YM1), source-limited wheat (YM25 and ZM27) maintained higher chlorophyll content, maximum net photosynthetic rate (Pnmax), and light energy utilization efficiency, and alleviated photoinhibition by reducing non-photochemical quenching (NPQ) and increasing the proportion of cyclic electron flow (CEF). Additionally, source-limited wheat flag leaves had higher carotenoid content and soluble protein content and stronger antioxidant capacity, which enabled them to scavenge reactive oxygen species, reduce membrane lipid peroxidation, and delay leaf senescence. N fertilization significantly improved wheat’s photosynthetic capacity and light energy utilization efficiency, alleviating photoinhibition. Source-limited wheat can still maintain the integrity of the photosynthetic apparatus under low N conditions by enhancing photoprotective mechanisms, showing stronger environmental adaptability. Therefore, proper N fertilization and optimization of source-sink relationships help improve wheat’s photosynthetic capacity and yield potential.